2006
DOI: 10.1177/0959-353506062970
|View full text |Cite
|
Sign up to set email alerts
|

‘You Couldn't Say “No”, Could You?’: Young Men's Understandings of Sexual Refusal

Abstract: While several psychological theories of rape have been developed, Tannen's ‘ miscommunication’ model is dominant, informing ‘expert’ and popular accounts alike. Rape is constructed as an extreme example of miscommunication – whereby women's ‘failure’ to say ‘no’ is interpreted by men as sexual consent. Kitzinger and Frith have demonstrated that young women have an implicit understanding of the normative interactional structure of refusal, and it is this that explains their difficulty in ‘just saying no’ to unw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
81
1

Year Published

2007
2007
2023
2023

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 117 publications
(89 citation statements)
references
References 35 publications
7
81
1
Order By: Relevance
“…The means of conveying consent or refusal mentioned by these participants are similar to previous findings (e.g. Beres, 2010;O'Byrne et al, 2006) that have demonstrated that non-verbal communication of consent and refusal is well understood by both young men and young women (Kitzinger & Frith, 1999;O'Byrne et al, 2006;O'Byrne et al, 2008). However, they also recognise that other people might read more into these behaviours (see 'Interpreting Consent' theme, below), and they also went on to emphasise the importance to them of verbal consent and refusal.…”
Section: (Sally)supporting
confidence: 61%
See 4 more Smart Citations
“…The means of conveying consent or refusal mentioned by these participants are similar to previous findings (e.g. Beres, 2010;O'Byrne et al, 2006) that have demonstrated that non-verbal communication of consent and refusal is well understood by both young men and young women (Kitzinger & Frith, 1999;O'Byrne et al, 2006;O'Byrne et al, 2008). However, they also recognise that other people might read more into these behaviours (see 'Interpreting Consent' theme, below), and they also went on to emphasise the importance to them of verbal consent and refusal.…”
Section: (Sally)supporting
confidence: 61%
“…Beres, 2007Beres, & 2010Hickman & Muehlenhard, 1999), people's ability to understand indirect and non-verbal sexual refusals (e.g. Kitzinger & Frith, 1999;O'Byrne et al, 2006), and factors that influence verdicts in court style judgements (e.g. Grubb & Harrower, 2008;Hammond et al, 2011).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations